Konseling Komunitas Kesehatan Mental di Lingkungan Kerja Kantor Urusan Agama Studi Kasus Pendekatan Preventif dan Interventif - Jamilah, Zamzam (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2025)
Mental health among employees and communities interacting with the Office of Religious Affairs (Kantor Urusan Agama/KUA) has become a crucial issue due to increasing workloads, family-related problems, and demands for value-based public services. KUA functions not only as an administrative religious institution but also as a strategic social space for strengthening mental and family resilience. This study aims to analyze the implementation of community-based mental health counseling in the KUA work environment and to evaluate its effectiveness through a case study approach. This research employed a qualitative method using a case study design, with data collected through participant observation, in-depth interviews, and documentation. The findings indicate that community counseling grounded in religious and cultural values at KUA enhances mental health awareness, reduces psychological stress, and strengthens both preventive and curative functions of religious services.